VISUAL NOVEL GAME BIMA’S ADVENTURE: DEVELOPMENT OF LEARNING MEDIA ON THE TOPIC OF EARTH ATMOSPHERIC LAYERS IN ELEMENTARY SCHOOL - Salsabilla, Zahra; Suryanti; Julianto; Istianah, Farida (INSECTA: Integrative Science Education and Teaching Activity Journal, 2025)
Several concepts in science subjects are abstract, making it difficult for students to understand the material and resulting in low learning outcomes. This issue is further exacerbated by the limited use of engaging learning media that support deep conceptual understanding. To address this issue, a visual novel-based learning media titled "Bima's Adventure" was developed for the topic of Earth's atmospheric layers. This study aims to determine the feasibility of the visual novel game "Bima's Adventure" as a learning medium to improve students' learning outcomes on the topic of Earth's atmospheric layers. The research employed a Research and Development (R&D) approach using the ADDIE model. The validation results showed a score of 93% (very valid) for media validation and 87% (very valid) for material validation. The trial results indicated that the media was efficient, based on teacher response questionnaires (96.9%) and student response questionnaires (92.89%). In addition, using this media significantly improved student learning outcomes, as evidenced by an N-Gain score of 0.71 (high) and a Mann-Whitney U-Test significance value of 0.000. Beyond improving academic performance, "Bima's Adventure" fostered student engagement through a problem-based learning approach.